Quantitative EEG as outcome measure of the therapeutic effects of transcranial pho-tobiomodulation: A systematic review - Magkouti, Eleni; Leventakis, Nikos; Alexandropoulou, Anna; Despoti, Akylina; Nanas, Serafim (Health & Research Journal, 2023)
Background: Transcranial Photobiomodulation (t-PBM) is a current, innovative method that is used in the therapy of many neurological and psychological diseases. Its mechanisms of action have been investigated and the most well described ways of action are its effects on mitochondrial function and on heat/light-activated ion channels on neurons membrane. It has been suggested that the increase in cerebral blood flow and the alterations of membrane ion channels are the most dominant potential mechanisms that cause the effects of PBM on quantitative electroencephalography (qEEG), that some recent studies have reported. Aim: The aim of this review is to describe the effects that t-PBM has on brain oscillations, as these are measured by qEEG. Methods: The research was carried out in the Pubmed database and it included all studies that had been published until February 2022. Results: Overall, sixty-eight studies were located and considered, searching with the terms Photobiomodulation or Light Therapy or Near Infrared Light and EEG. Only eleven of them used Photobiomodulation in order to observe the effect it can have on human brain oscillations, measured by qEEG. Two studies reported the EEG alterations after t-PBM application on the hand instead of the head. Thus, nine studies were included in the review, which applied t-PBM and observed the alterations that it brought upon qEEG of healthy adults or patients with memory problems. Conclusion: The studies showed that t-PBM increases high frequency neural activity and inhibits low frequency oscillations. The studies varied a lot in the ways of light application and the parameters of the light itself, as well as on their study population.